PELE: Power Efficient Legitimate Eavesdropping via Jamming in UAV Communications - Wang, Xiaoming (2017)
13th International Wireless Communications and Mobile Computing Conference (IWCMC 2017). 26 to 30, Jun, 2017, Vehicular Communications Symposium. Valencia, Spain.